Evaluating the effects of exchange rate volatility on knitwear export performance to assess economic growth in Bangladesh - Tanushree Basak; Ashiqur Rahman; Md Nazmus Sadekin; Khan Sarfaraz Ali (Discover Sustainability, 2025)
Abstract The exchange rate is an essential determinant of exports in any country, and export plays a vital role in driving a country’s economy. Nowadays, the variation of the exchange rate has become a highlighted topic. This paper explores the relationship between the Exchange Rate Volatility and the most exported item of Bangladesh, Knitwear Exports. This study also wants to check the connection between Bangladesh's Exchange Rate and Knitwear Exports. The study is based on secondary data for the period 1994–2022. To achieve the objectives, this study uses Knitwear exports as endogenous variables and the official exchange rate, inflation rate, and exchange rate volatility as the exogenous variables. The data are collected from the World Development Index (WDI) and the Bangladesh Garment Manufacturers and Exporters Association (BGMEA)). To effectively analyze the relationship between variables with potential mixed orders of integration, this study employs the Autoregressive Distributed Lag (ARDL) bound test. The ARDL bound test's ability to accommodate mixed-stationary data without pre-testing and its direct estimation of long-run and short-run effects make it a suitable choice for this analysis. The findings of this paper show that the exchange rate volatility negatively and significantly influences Knitwear exports in the short run with the elasticity 0.119. But in the long term, the result shows a positive but insignificant impact (elasticity: − 0.211). This study also shows that the exchange rate has a significant beneficial linkage with the exports of knitwear products in the long run. This paper recommends that although depreciation of the exchange rate has a beneficial influence on exports, it may prove harmful to other sectors of the economy. And Investment in the knitwear sector can lead to a boom in the economy of Bangladesh.